1985
DOI: 10.1073/pnas.82.11.3859
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol myristate acetate inhibits thrombin-stimulated Ca2+ mobilization and phosphatidylinositol 4,5-bisphosphate hydrolysis in human platelets.

Abstract: The tumor-promoting phorbol diester 4,8-phorbol 12-myristate 13-acetate (PMA) inhibited mobilization of intracellular Ca2' in platelets by thrombin (also trypsin and 1-O-alkyl-2-acetyl-sn-glyceryl-3-phosphocholine). PMA was effective over the same concentration range that activates protein kinase C in intact platelets; ICse vs. thrombin = 2 ng/ml, 3.4 nM: >90% inhibition at 10-20 ng/ml. Suppression of thrombin-induced Ca2' mobilization was evident within 30 sec of pretreatment with PMA and was essentially comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
51
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(63 citation statements)
references
References 33 publications
12
51
0
Order By: Relevance
“…It is significant that, apart from the potentiatory effects described above, OAG had no inhibitory effect on thrombin-induced rise in [Ca2+Ji at both low and high thrombin concentrations and this represents a major divergence in the effects of GAG and phorbol esters, which have been shown to inhibit agonist-induced [Ca'+]i mobilisation in platelets [1,2]. Furthermore OAG had no significant effect on high-dose thrombin-induced…”
Section: Discussionmentioning
confidence: 89%
“…It is significant that, apart from the potentiatory effects described above, OAG had no inhibitory effect on thrombin-induced rise in [Ca2+Ji at both low and high thrombin concentrations and this represents a major divergence in the effects of GAG and phorbol esters, which have been shown to inhibit agonist-induced [Ca'+]i mobilisation in platelets [1,2]. Furthermore OAG had no significant effect on high-dose thrombin-induced…”
Section: Discussionmentioning
confidence: 89%
“…Subsequently, we have clarified that protein kinase C has additionally an antiproliferative action in this cell type, and have proposed that this enzyme may serve as not only a positive but also a negative regulator in the proliferation of rabbit aortic SMCs [10]. During the course of these studies, we have found that protein kinase C inhibits the WBS-induced increase in [Ca2+]i in rabbit aortic SMCs as described in several cell types [11][12][13][14][15]. Moreover, we have found that protein kinase C is partially downregulated by prolonged treatment of rabbit aortic SMC with PDBu, and that the partial downregulation of protein kinase C abolishes completely both the proliferative and antiproliferative actions of this enzyme but does not abolish the inhibitory action of this enzyme in the regulation of [Ca2*]i.…”
Section: Published By Elsevier Science Publishers Bv (Biomedical DImentioning
confidence: 88%
“…5]. However these kinases have a large variety of different molecular targets in platelets that could mediate the effect of this kinase on platelet Ca 2+ signalling, with a number of publications suggesting a variety of mechanisms including inhibition of phospholipase C [6,7], stimulation of inositol-1,4,5-trisphosphate (IP 3 ) breakdown [8,9], stimulation of the plasma membrane Ca 2+ -ATPase (PMCA) [10,11], stimulation of sarco/endoplasmic reticulum Ca 2+ -ATPases (SERCAs) [12] and in the case of ADP, desensitization of the receptor [13]. Since inhibition of PMCAs does not abolish the potentiatory effect of PKC inhibitors on thrombin-evoked Ca 2+ rises, PMCAs do not appear to be involved in the response [14].…”
Section: Introductionmentioning
confidence: 99%